The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/2359-3997000000126
|View full text |Cite
|
Sign up to set email alerts
|

Maternal 75-g OGTT glucose levels as predictive factors for large-for-gestational age newborns in women with gestational diabetes mellitus

Abstract: Objective: Our goal was to investigate which glucose measurement from the 75-g oral glucose tolerance test (OGTT) has more capability of predicting large for-gestational-age (LGA) newborns of mothers with gestational diabetes mellitus (GDM). Subjects and methods: The study group consisted of 118 consecutively pregnant women with singleton pregnancy, patients of Outpatients Department of the Endocrinology, Diabetes, and Metabolic Disorders Clinic. All were prospectively screened for GDM between 24 th and 28 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Silva et al have also identified high levels of plasma glucose at the 2-hour measurement in the OGTT as one of the major independent risk factors for LGA newborns. 19 Brankica et al 35 and Ouzilleau et al 37 found high levels of fasting blood glucose to be better predictors, whereas Mello et al 38 showed that 1-hour blood glucose was the factor most closely associated with LGA newborns. 35,37,38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al have also identified high levels of plasma glucose at the 2-hour measurement in the OGTT as one of the major independent risk factors for LGA newborns. 19 Brankica et al 35 and Ouzilleau et al 37 found high levels of fasting blood glucose to be better predictors, whereas Mello et al 38 showed that 1-hour blood glucose was the factor most closely associated with LGA newborns. 35,37,38…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of LGA newborns was significantly higher in the group of women with combined change in the OGTT (fasting þ after the dextrose load), even after the multivariate analysis. Brankica et al 35 found that the combination of fasting blood glucose and blood glucose 1 hour after the glucose load in the OGTT was a predictor of occurrence of LGA newborns. Pregnant women exhibiting this combination may be considered at increased risk because of the fact that they have two distinct changes, altered fasting glucose and glucose intolerance, which suggests impairment in two different metabolic pathways associated with the disease, dysfunction of pancreatic β cells and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study reported that between January 2016 and July 2016, 21.8% pregnant women were diagnosed with GDM based upon the criteria of the International Association of Diabetes and Pregnancy Study Groups (IADPSG) in some areas 15 . Most studies have investigated the relationship between GDM and gestational outcome 16 , 17 , which suggested that infants born to GDM mothers had higher weight or greater risk of large for gestational age (LGA). However, there exist some problems in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…11 Abdalrahman et al have concluded from their study that gestational diabetes mellitus, even when controlled also can lead to higher number of LGA babies. 12 In our current study also there was a significant association of LGA babies in pregnant women with gestational diabetes (p=0.05).…”
Section: Discussionmentioning
confidence: 98%